2017
DOI: 10.1016/j.msec.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Novel electrospun nanofibers of modified gelatin-tyrosine in cartilage tissue engineering

Abstract: In natural cartilage tissues, chondrocytes are linked to extracellular matrix (ECM) through cell-surface binding proteins. Surface modification of gelatin can provide a new generation of biopolymers and fibrous scaffolds with chemical, mechanical, and biological properties. In this study tyrosine protein and 1,2,3-triazole ring were utilized to functionalize gelatin without Cu catalyst. Their molecular structure was characterized by Fourier transform infrared spectroscopy (FTIR) and nuclear magnetic resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 68 publications
1
36
0
Order By: Relevance
“…Aiming to mimic the nanofibrous architecture of the extracellular matrix (ECM) of biological tissues, gelatin has been successfully electrospun into nanofibrous membranes. In light of its non-toxicity, biodegradability, biocompatibility, formability and low-cost commercial availability [20], gelatin has been excessively used as building block for the design of smart wound dressing and healing materials [21,22], pharmaceuticals [23], personal care [24] and food industry products [25], as well as drug delivery systems [26][27][28] and scaffolds for tissue engineering [29]. However, electrospun gelatin typically present uncontrollable water-induced swelling and dissolution, and display weak mechanical strength in the hydrated state, which substantially limit long-term fibre performance [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aiming to mimic the nanofibrous architecture of the extracellular matrix (ECM) of biological tissues, gelatin has been successfully electrospun into nanofibrous membranes. In light of its non-toxicity, biodegradability, biocompatibility, formability and low-cost commercial availability [20], gelatin has been excessively used as building block for the design of smart wound dressing and healing materials [21,22], pharmaceuticals [23], personal care [24] and food industry products [25], as well as drug delivery systems [26][27][28] and scaffolds for tissue engineering [29]. However, electrospun gelatin typically present uncontrollable water-induced swelling and dissolution, and display weak mechanical strength in the hydrated state, which substantially limit long-term fibre performance [30].…”
Section: Introductionmentioning
confidence: 99%
“…In light of the presence of amine and carboxylic groups along gelatin backbones, various chemical treatments have been proposed to introduce covalent crosslinks lost following collagen extraction and denaturation ex vivo, so that micro-/macroscopic structural features and mechanical properties of hydrated gelatin nanofibre membranes could be controlled [31]. Crosslinking strategies have been pursued by carbodiimide chemistry [29,[32][33][34], bifunctional compounds such as glutaraldehyde (GTA) [33,[35][36][37][38][39][40][41][42] and genipin [30,43,44], silanisation [41], dehydrothermal [46] and plasma treatments [47], as well as via ultraviolet (UV) light [30,[48][49][50]. Although chemical crosslinking is the most widely used method, crosslinking agents are often associated with risks of cytotoxicity and calcification in host polymer scaffolds [51][52][53], are unable to ensure fibrous retention and minimal membrane dissolution in aqueous media [30,48,54], may cause thermal degradation of gelatin [55,56], or may lead to side reactions, resulting in hardly-controllable process-structure-property relationships.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro cell culture results revealed that electrospun engineered protein scaffolds supported the attachment and growth of chondrocytes. These nanofibers also showed cell proliferation suggesting their applicability in cartilage engineering . Porous and biocompatible nanocomposite scaffolds of cellulose nanofibers stabilized using a mixture of crosslinked gelatin and chitosan has been synthesized.…”
Section: Cartilage Tementioning
confidence: 99%
“…These nanofibers also showed cell proliferation suggesting their applicability in cartilage engineering. 111 Porous and biocompatible nanocomposite scaffolds of cellulose nanofibers stabilized using a mixture of crosslinked gelatin and chitosan has been synthesized. The developed nanocomposites possessing good cytocompatibility, high porosity, and ability to tailor mechanical properties have been proposed to provide cell attachment to chondrocytes and form ECM for cartilage engineering.…”
Section: Cartilage Tementioning
confidence: 99%
“…This polymer has devoted a great interest of academic researchers and market demand to itself. It produces excellent films, fibers, hydrogels forming, emulsifying, adhesive properties, solubility in water, biodegradability and etc .…”
Section: Introductionmentioning
confidence: 99%